Improving Learning Outcomes of Student’s Volleyball Arbitration using the Team Games Tournament Learning Model - Pnatmo Welhelmina Masi; Magdalena Rambu Pisu Wasak (STKIP Muhammadiyah Kuningan, 2020)
The purpose of this study is to improve the learning outcomes of student volleyball arbitration using the Team Games Tournament learning model. This study uses a class action research design from S. Kemmis and R. McTaggart involving 40 students. Data were taken using a test of learning outcomes then were analyzed through descriptive quantitative method. It showed that student learning outcomes have increased in the action of cycle 3. The increasing of learning outcomes in cycle 1 to cycle 2 was 15% because the students were getting used to the TGT learning model and cycle 2 to cycle 3 was 62.5% because the educator, practitioners and the students collaborated intensely doing exercises, simulations and demonstrations so as to help them understand and practice how to referee the game of volleyball. Conclusion of this research is the TGT learning models with the practitioner’s involvement in the form of simulation and demonstration of arbitration can be applied by educators to improve students learning outcomes based on knowledge and skills.